How Does FoMO Boost the Usage of Mobile Payment Apps? Developing a Conceptual Model Using Causality Orientation Theory - Biswas, Wendrila; Giri, Arunangshu (Prabandhan: Indian Journal of Management, 2026)
Purpose : The paper explored how the crucial facets of the Fear of Missing Out (FoMO) phenomenon affected different motivational orientations––autonomous, control, and impersonal––– toward an urge of unintended and immediate purchase, triggering the usage of m-payment apps. Design/Methodology/Approach : In this study, qualitative analysis based on the in-depth semi-structured interview method was used to develop a conceptual model with the help of Causality Orientation Theory (COT). We used NVIVO-15 software for analyzing qualitative data through word clouds and hierarchy charts. Findings : A conceptual model was developed to identify the FoMO-based compulsive and impulsive buying behavior impacting the usage of mobile payment apps. Also, this study acknowledged two factors––online social comparison and social anxiety––that affected FoMO- based compulsive buying behavior and two factors––harmonious passion and obsessive passion that affected FoMO-based impulsive buying behavior. Implications : The insights provided in the study would unveil a significant pathway for redesigning and reforming marketing strategies and customer segmentation for companies ahead. But initially, the deeper understanding of the study would advance the Fintech firms to accelerate the user acceptance and adoption of m-payments apps on a substantial scale, along with an upscale of their investors. Originality/Value : The study provided unique perspectives on the effect of FoMO as an antecedent. The psychological responses of the customers (social anxiety, online social comparison, harmonious, and obsessive passion) are well delineated in the study, which significantly affected the usage of m-payment apps through FoMO-based compulsive and impulsive buying.